RAGAM GENETIK TIGA POPULASI SEPAT SIAM (Trichopodus pectoralis Regan; Osphronemidae) ASAL KALIMANTAN MENGGUNAKAN ANALISIS RAPD DAN PENGUKURAN MORPHOMETRIC TRUSS - Iskandariah Iskandariah; Dinar Tri Soelistyowati; Rudhy Gustiano; Irin Iriana Kusmini; Gleni Hasan Huwoyon (BERITA BIOLOGI, 2015)
The aim of this study was to evaluate the genetic diversity of three populations of Snakeskin Gourami (Trichopodus pectoralis;Osphronemidae)from three provinces of Indonesian Borneo:West, Central, and South Kalimantan using Random Amplified Polymorphism DNA (RAPD) and morphometric truss methods.DNA amplification using primer OPC-02,OPC-05,and OPA-09 resulted in 21 to 28 fragments with sizes ranged from 200 to 1600 bp, polymorphism value was of 7.14 to 25.00%, heterozygosity was of 0.02 to 0.11 and the genetic distance between populations was of 0.27 to 0.28.Truss morphometrics analysis showed that the coefficient of variability was ranging between 2.75 to 12.52%.There were 9 characters that can be used as diagnostic characters for Snakeskin Gourami. The intra population similarity index in Snakeskin Gourami populations from West Kalimantan was the highest (80%) followed by populations from Central Kalimantan (16.7%) and South Kalimantan (3.3%).The results of RAPD and truss morphometric analysis suggested that populations from West Kalimantan have higher genetic diversity than populations from Central and South Kalimantan.